2016
DOI: 10.1021/acs.jpcc.6b08473
|View full text |Cite
|
Sign up to set email alerts
|

Water Splitting on Transition Metal Active Sites at TiO2-Based Electrodes: A Small Cluster Study

Abstract: We investigate the influence of doping TiO2 surfaces with transition metals (TMs) on the performance of TiO2-based electrodes for the water-splitting electrochemical reaction. Two cluster models of the TM-doped active sites which resemble both the TiO2 anatase (001) and rutile (110) surfaces are considered for the evaluation of the water decomposition reaction when a Ti is replaced by a TM atom. These models constitute a direct extension from our previous work in which similar representations were employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…S2 in the ESI†). 18 In B02 , the molecular adsorption of H 2 O due to the Bi⋯O interaction with a distance of 2.688 Å occurred, and this was analogous to the DFT results obtained by Li and coworkers. 15 The first deprotonation from the adsorbed H 2 O was largely endergonic ( B03 ), as in the corresponding step on TiO 2 ( T02 → T03 , Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…S2 in the ESI†). 18 In B02 , the molecular adsorption of H 2 O due to the Bi⋯O interaction with a distance of 2.688 Å occurred, and this was analogous to the DFT results obtained by Li and coworkers. 15 The first deprotonation from the adsorbed H 2 O was largely endergonic ( B03 ), as in the corresponding step on TiO 2 ( T02 → T03 , Fig.…”
Section: Resultssupporting
confidence: 81%
“…In this study, we focus on the photoinduced oxidation of H 2 O and carbonic acid (H 2 CO 3 ) on TiO 2 and BiVO 4 using quantum chemical calculations at the DFT level. According to a commonly accepted theoretical description that consists of four proton-coupled electron-transfer (PCET) steps with two H 2 O molecules, 14–19 the intermediate and oxidation mechanisms of H 2 CO 3 , as well as H 2 O, are investigated using molecular cluster models. By identifying the cause of the effect of carbonate, the variety of available photocatalysts/photoelectrodes and that of the products from H 2 O and solar energy for sustainable development should be extended.…”
Section: Introductionmentioning
confidence: 99%
“…The large overpotential required for the OER is known to be a serious restraint to PEC water splitting and has motivated many investigations for finding efficient ways to lower it (see, e.g., ref for a review). Because of its many beneficial properties, such as chemical and optical stability, nontoxicity, low cost, as well as abundance, TiO 2 has been one of the most studied photoanode materials. A few studies have shown that water splitting on TiO 2 also suffers from such large overpotentials, especially on the anatase surface, where overpotentials larger than 1 eV have been recorded for the OER. , …”
Section: Introductionmentioning
confidence: 99%
“…5−7 A few studies have shown that water splitting on TiO 2 also suffers from such large overpotentials, especially on the anatase surface, where overpotentials larger than 1 eV have been recorded for the OER. 8,9 Several recipes have been proposed to reduce the OER overpotential on TiO 2 and to broaden the light absorption spectra so as to cover the visible region. One such recipe is to couple TiO 2 with Cu 2 O and CuO nanoparticles or clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Unstable semiconductors are being coated with nanometer scale thin films of materials including metals or metal silicides, [106][107][108][109] wide band gap semiconductors, 110 transparent conducting oxides, 111,112 transition metals and their oxides, 113,114 and organic polymers. 115 Most recent studies deal with the fabrication of these using ALD, 116 which allows for ultra-thin films with limited charge transfer resistance.…”
Section: Conventional Protection Mechanisms For Photoelectrodesmentioning
confidence: 99%